Beyond Judicial Review: Constitutional Court Decision No. 62/PUU-XXII/2024 as a Landmark Decision - Baharuddin Riqiey; Yuriadi (Jurnal Mengkaji Indonesia, 2026)
Abstract: The regulation of the presidential threshold has consistently been regarded by the Indonesian Constitutional Court as falling within the exclusive domain of the legislature, as reflected in at least 34 prior decisions. However, both constitutional theory and practice acknowledge that courts may depart from established positions when confronted with new legal and social realities. Such decisions, which significantly shift judicial reasoning, are often characterized as landmark decisions. Despite the importance of this concept, there remains a gap in systematically assessing whether specific Constitutional Court rulings meet the established criteria of a landmark decision, particularly in the Indonesian context. This study addresses that gap by evaluating Constitutional Court Decision Number 62/PUU-XXII/2024 against the criteria proposed by Amran Suadi. The findings demonstrate that the decision satisfies all five key criteria, namely final and binding authority, the presence of legal discovery, responsiveness to evolving social dynamics, contribution to the direction of legal development, and its unprecedented nature in judicial reasoning. Accordingly, this decision can be classified as a landmark decision with significant doctrinal and practical implications for Indonesian constitutional law. Purpose: This study aims to evaluate whether Constitutional Court Decision Number 62/PUU-XXII/2024 qualifies as a landmark decision based on established legal criteria. Design/Methodology/Approach: This research employs a normative legal method, utilizing a statutory, conceptual, and case-based approach to analyze the decision in light of relevant legal doctrines and scholarly frameworks. Findings: The study finds that Decision Number 62/PUU-XXII/2024 fulfills all criteria of a landmark decision, including its binding nature, innovative legal reasoning, responsiveness to societal changes, influence on future legal development, and its departure from prior judicial positions. Originality/value: This research offers a systematic application of landmark decision criteria within the Indonesian constitutional context, providing a structured evaluation that contributes to the development of constitutional jurisprudence and judicial analysis.